Penguatan Peran Perempuan dalam Pendidikan di Pesantren Muhammadiyah - Tricahyo, Agus; Zubaidi, Ahmad; Prakoso, Darmawan Ilham (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
This research was conducted to empower ustadzah in Muhammadiyah Islamic boarding schools through an empowerment program to read the bald book, by applying the Participatory Action Research (PAR) method for five months, from March to the end of July 2021. The results of the research show that the ustadzah are very active in da'wah and general education activities through the Muhammadiyah association. However, the majority of Muhammadiyah Islamic boarding school ustadzah lack competence in reading Arabic books which are the main focus of Islamic boarding school learning. The program that was implemented to empower reading the bald book was successful in increasing the ability to read the bald book simply among ustadzah. Based on these results, researchers provide several suggestions. This research was conducted to empower ustadzah in Muhammadiyah Islamic boarding schools through an empowerment program to read the bald book, by applying the Participatory Action Research (PAR) method for five months, from March to the end of July 2021. The results of the research show that the ustadzah are very active in da'wah and general education activities through the Muhammadiyah association. However, the majority of Muhammadiyah Islamic boarding school ustadzah lack competence in reading Arabic books which are the main focus of Islamic boarding school learning. The program that was implemented to empower reading the bald book was successful in increasing the ability to read the bald book simply among ustadzah. Based on these results, researchers provide several suggestions. Islamic boarding schools are advised not to involve ustadzah too much in activities outside of Islamic boarding school activities so that they can focus more on increasing Islamic boarding school competency. Apart from that, Islamic boarding schools need to continue to improve the abilities of their ustadzahs through upskilling efforts in mastering Arabic books. Simultaneous follow-up to programs that have been implemented is also needed. If weaknesses are found in future program implementation, a review needs to be carried out using appropriate research methods. In this way, efforts to empower ustadzah can continue to develop and make a greater contribution to Islamic boarding school learning.